Implementasi Pelatihan dan Pengembangan Karyawan Bank Sumut KCP Deli Tua dalam Meningkatkan Kinerja Karyawan pada Masa Pandemi Covid-19 - Prengki Jans Nababan; Onan Marakali Siregar (International Journal Labs, 2022)
The Pandemic Covid-19 had a bad influence on the performance of employees at Bank Sumut KCP Deli Tua. The COVID-19 pandemic has resulted in a decrease in employee performance, resulting in a decrease in the achievement of work targets. Bank Sumut KCP Deli Tua improves employee performance through training and employee development to stay productive during the pandemic Covid-19. This study aims to find out the implementation of training and development of Bank Sumut KCP Deli Tua employees during the pandemic Covid19. This study will also examine whether the implementation of employee training and development conducted by Bank Sumut KCP Deli Tua has been effective in improving employee performance during the pandemic Covid-19. This research uses a descriptive method with a qualitative approach, namely by describing events or facts contained in the object of research by conducting interviews and documentation, then analyzing the data obtained from the research location and comparing it with theory. Based on the results of the study, it can be concluded that Bank Sumut KCP Deli Tua conducted employee training during the pandemic Covid-19 using direct work practices, online training, and simulation methods. Bank Sumut KCP Deli Tua also conducts employee development with education and training methods. The implementation of this training and development has proven to be effective in improving employee performance during the pandemic Covid-19. After participating in training and development, employees work more enthusiastically and employees succeed in achieving the work targets that have been determined.